THE FRAME ORGANIZATION OF PROVERBIAL EXPRESSIONS REPRESENTING THE CONCEPT OF MONEY IN RUSSIAN AND FRENCH LINGUISTIC CULTURES - Zalavina, Tatyana (Revista Inclusiones, 2020)
This article examines proverbial units in relation to the concept viewed as the cognitive structure of knowledge. The relevance of this research area derives from theoretical and practical issues in modern linguistics that focuses on linguistic identity, interaction between language and culture as well as the linguistic worldview encrypted in the language in general and in the proverbial lexicon in particular. Language reinforces and implements the results of human reflective mental activities. Proverbs and sayings most clearly demonstrate this point, as they represent the distinctive features of the mentality, cognition and worldview of a nation speaking a specific language, along with its cultural values. The study focuses on the following objectives: determining basic representations of the conceptual content of the notion of money; identifying lexical units that are representative of this concept in Russian and French linguistic mentalities; classifying proverbs according to frames reflecting the multidimensional content of proverbs related to the concept under investigation; and describing the universal and national components of importance for the linguistic awareness of the Russians and the French. The author used a method known as the definitional analysis with a view to identify the main points of the conceptual content of the notion of money and the corpus of lexical representatives of the concept under consideration. The above-mentioned method revealed that basic representations of the conceptual content of the notion of money and comparisons of Russian and French dictionary entries for ‘money’ / ‘argent’ generally coincide. The concept of MONEY verbalized by Russian and French proverbial units can be regarded as a special type of proverbial concepts. Combining several research methods, including the definitional analysis, the cognitive and semantic analysis of proverbs and the frame classification of proverbs proved to be a highly fruitful approach. Frames are an efficient way to transmit information and to speed up its processing, given that they contain both apparent and hidden/implied data.